Faktor-Faktor yang Mempengaruhi Niat untuk Mengunjungi Tempat Hiburan Selama Pandemi Covid-19 - Nur Faizi; Muhamad Suharjo; Freddy Pungky Putra; Muhammad Luthfi Akbar; Usep Suhud (Jurnal Bisnis, Manajemen, dan Keuangan, 2021)
This study aims to examine the factors that influence a person's intention to visit entertainment venues during the COVID-19 pandemic. There are six variables used to test these factors, namely distance, wellbeing, hedonism, having fun, socializing, and place image. Data collection were carried out in Jakarta during the COVID-19 pandemic situation and the transitional PSBB (Large-Scale Social Restrictions) period in September 2020. Data was collected using an online questionnaire and respondents were selected using a purposive sampling technique. The total respondents in this study were 225 consisting of 82 men and 143 women who all live in Jakarta. This data is processed by exploratory factor analysis and structural equation models. As a result, distance, wellbeing, having fun, socializing, and place image did not have a significant effect on visit intention. Meanwhile, hedonism is rejected because it is invalid. Penelitian ini bertujuan untuk menguji faktor-faktor yang mempengaruhi niat seseorang untuk mengunjungi tempat hiburan selama masa Pandemi COVID-19. Ada enam variabel yang digunakan untuk menguji faktor-faktor tersebut, yaitu distance, wellbeing, hedonism, having fun, socializing, dan place image. Pengumpulan data dilakukan di Jakarta di situasi pandemi COVID-19 dan masa PSBB (Pembatasan Sosial Berskala Besar) transisi di bulan September 2020. Data dikumpulkan dengan menggunakan kuesioner daring dan responden dipilih dengan menggunakan teknik purposive sampling. Total responden dalam penelitian ini adalah 225 yang terdiri dari 82 laki-laki dan 143 perempuan yang seluruhnya berdomisili di Jakarta. Data ini diolah dengan exploratory factor analysis dan structural equation model. Hasilnya, distance, wellbeing, having fun, socializing, dan place image tidak memiliki pengaruh yang signifikan terhadap visit intention. Sedangkan, hedonism ditolak karena tidak valid.